Acute isolated posterior cerebral artery stroke treated with mechanical thrombectomy: A single-center experience and review of the literature. Issue 1 (February 2023) - Baig, Ammad A; Monteiro, Andre; Waqas, Muhammad; Cappuzzo, Justin M; Siddiqi, Manhal; Doane, Jacob; Dossani, Rimal H; Almayman, Faisal; Khawar, Wasiq I; Davies, Jason M; Snyder, Kenneth V; Levy, Elad I; et al.
Background: Acute isolated posterior cerebral artery (PCA) occlusions account for 5–10% of all ischemic events. Due to peculiar patient presentation, the potential benefit of mechanical thrombectomy (MT) remains controversial. We evaluated the safety, feasibility, and effectiveness of MT in our patients and compared our results with the literature review conducted. Methods: Charts were reviewed retrospectively for consecutive patients diagnosed with acute PCA stroke who underwent MT. Demographics, procedural, and follow-up details were noted. For the literature review, a systematic search of PubMed, MEDLINE, and EMBASE databases was conducted for the keywords "posterior cerebral artery" and "thrombectomy" for articles published between January 1, 2010 and June 30, 2021. Estimated rates for recanalization, favorable outcomes (modified Rankin Scale [mRS] score 0–2), symptomatic intracerebral hemorrhage (sICH), and mortality were extracted. Results: Our cohort included 21 patients. Mean age was 71.2 years (standard deviation [SD] ± 10.2). Median National Institutes of Health Stroke Scale (NIHSS) presentation score was 9 (interquartile range [IQR] 5–15), with visual symptoms reported in 12(57.1%) patients. Overall, final modified thrombolysis in cerebral infarction (mTICI) 2b-3 was achieved in 17 patients (80.9%) with first-pass mTICI 2b-3 attained in 8 (38.1%). Postprocedure sICH occurred in 1 (4.8%) patient. Fifteen (71.4%) patients had a 0–2 mRS score at 90 days. Visual symptoms resolved in 10 of 12(83.3%) patients. Mortality occurred in 2 (9.5%) patients. For the systematic review, cohorts from 4 articles plus ours were included, totaling 222 patients. The estimated rate of successful recanalization was 85.25% (95% confidence interval[CI], 73.05%–97.45%), sICH was 3.60% (95% CI, 1.11%–6.09%), and mortality was 10.51% (95% CI, 5.88%–15.15%). Conclusion: The results of our series and systematic review indicate MT as a potentially safe and effective treatment modality for acute PCA stroke. These results also indicate that patient selection and assessment may be the key in obtaining favorable outcomes.